2022
DOI: 10.1002/pits.22836
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the HORS‐PISTE universal anxiety prevention program measured according to initial level of student problems

Abstract: Anxiety disorders are among the most prevalent psychopathologies in Western adolescents and have been on the rise in recent years. Not only does anxiety disrupt the daily lives of the young people who suffer from it, it can also have harmful behavioral, psychological, social, and academic effects. Given this, there is a pressing need to implement universal anxiety prevention programs for adolescents in one of their main living environments, the school. This type of program has the twofold advantage of reaching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
1
1
0
Order By: Relevance
“…These findings are supported by other studies conducted in the pandemic context (Decosimo et al, 2019;Gresham et al, 2021;Mirabito & Verhaeghen, 2024). They are also supported by the results shown in an evaluation of the program carried out before the pandemic that suggest that the program contributes to a positive change regarding the anxiety and depression symptoms, as well as key proximal risk factors, as Therriault et al (2023) showed.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These findings are supported by other studies conducted in the pandemic context (Decosimo et al, 2019;Gresham et al, 2021;Mirabito & Verhaeghen, 2024). They are also supported by the results shown in an evaluation of the program carried out before the pandemic that suggest that the program contributes to a positive change regarding the anxiety and depression symptoms, as well as key proximal risk factors, as Therriault et al (2023) showed.…”
Section: Discussionsupporting
confidence: 86%
“…Previous evaluations of the universal prevention component have shown a decrease in symptoms related to various anxiety disorders, as well as reductions in perfectionism, intolerance of uncertainty, cognitive avoidance, and impact of anxiety on school and social life, along with an increase in feelings of self-efficacy (Therriault et al, 2023). The program was implemented in more than 20 high schools during the COVID-19 pandemic, and the objective of the present article is to measure its contribution in the pandemic context to several anxiety-related variables, specifically: (1) anxiety symptoms and interference; (2) cognitive and behavioral vulnerabilities targeted by the program; and 3) associated symptoms and behaviors.…”
Section: Introductionmentioning
confidence: 99%